Mavacamten for treatment of symptomatic obstructive hypertrophic cardiomyopathy (EXPLORER-HCM): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 10253 (12th September 2020) - Olivotto, Iacopo; Oreziak, Artur; Barriales-Villa, Roberto; Abraham, Theodore P; Masri, Ahmad; Garcia-Pavia, Pablo; Saberi, Sara; Lakdawala, Neal K; Wheeler, Matthew T; Owens, Anjali; Kubanek, Milos; Wojakowski, Wojciech; et al.
Summary: Background: Cardiac muscle hypercontractility is a key pathophysiological abnormality in hypertrophic cardiomyopathy, and a major determinant of dynamic left ventricular outflow tract (LVOT) obstruction. Available pharmacological options for hypertrophic cardiomyopathy are inadequate or poorly tolerated and are not disease-specific. We aimed to assess the efficacy and safety of mavacamten, a first-in-class cardiac myosin inhibitor, in symptomatic obstructive hypertrophic cardiomyopathy. Methods: In this phase 3, randomised, double-blind, placebo-controlled trial (EXPLORER-HCM) in 68 clinical cardiovascular centres in 13 countries, patients with hypertrophic cardiomyopathy with an LVOT gradient of 50 mm Hg or greater and New York Heart Association (NYHA) class II–III symptoms were assigned (1:1) to receive mavacamten (starting at 5 mg) or placebo for 30 weeks. Visits for assessment of patient status occurred every 2–4 weeks. Serial evaluations included echocardiogram, electrocardiogram, and blood collection for laboratory tests and mavacamten plasma concentration. The primary endpoint was a 1·5 mL/kg per min or greater increase in peak oxygen consumption (pVO2 ) and at least one NYHA class reduction or a 3·0 mL/kg per min or greater pVO2 increase without NYHA class worsening. Secondary endpoints assessed changes in post-exercise LVOT gradient, pVO2, NYHA class, Kansas City Cardiomyopathy Questionnaire-Clinical Summary Score (KCCQ-CSS), and Hypertrophic Cardiomyopathy Symptom Questionnaire Shortness-of-Breath subscore (HCMSQ-SoB). This study is registered with ClinicalTrials.gov, NCT03470545 . Findings: Between May 30, 2018, and July 12, 2019, 429 adults were assessed for eligibility, of whom 251 (59%) were enrolled and randomly assigned to mavacamten (n=123 [49%]) or placebo (n=128 [51%]). 45 (37%) of 123 patients on mavacamten versus 22 (17%) of 128 on placebo met the primary endpoint (difference +19·4%, 95% CI 8·7 to 30·1; p=0·0005). Patients on mavacamten had greater reductions than those on placebo in post-exercise LVOT gradient (−36 mm Hg, 95% CI −43·2 to −28·1; p<0·0001), greater increase in pVO2 (+1·4 mL/kg per min, 0·6 to 2·1; p=0·0006), and improved symptom scores (KCCQ-CSS +9·1, 5·5 to 12·7; HCMSQ-SoB −1·8, −2·4 to −1·2; p<0·0001). 34% more patients in the mavacamten group improved by at least one NYHA class (80 of 123 patients in the mavacamten group vs 40 of 128 patients in the placebo group; 95% CI 22·2 to 45·4; p<0·0001). Safety and tolerability were similar to placebo. Treatment-emergent adverse events were generally mild. One patient died by sudden death in the placebo group. Interpretation: Treatment with mavacamten improved exercise capacity, LVOT obstruction, NYHA functional class, and health status in patients with obstructive hypertrophic cardiomyopathy. The results of this pivotal trial highlight the benefits of disease-specific treatment for this condition. Funding: MyoKardia.